REACTOR OPERATIONAL EXPERIENCE REVIEW AND ANALYSIS BASED ON UN-INTENDED REACTOR TRIP DATA - Sigit Santoso; Roziq Himawan; Johnny Situmorang; Tulis Jojok Suryono; Edison Edison (Pusat Teknologi Dan Keselamatan Reaktor Nuklir (PTKRN), 2019)
To enhance the safety and reliability of a new reactor, human factors should be integrated into its design process. The experimental power reactor (RDE) currently being developed in Indonesia needs to include human factors in the design process. One approach to incorporate human factors into design is by considering reactor operational experience data. This paper reviews and analyses the operational experience data of RSG-GAS reactor. The operational experience data of RSG-GAS reactor with 40,435 hours of total operation time spanning from 2003 to 2013 was used as a base in the study. In depth analysis on human factors was applied to the primary cooling system using Human Factors Analysis and Classification System-HFACS method. An amount of 289 un-intended trips were found in the observation data period. Most of un-intended trip were caused by external factors (38%). A review on the primary and secondary cooling system operational data showed that 3.11% of un-intended reactor trip occurrence causes were associated with human failure. Most suspected human failure/human error corresponds to the pump maintenance task which is classified as A action category. Analysis on the cooling system based on HFACS showed that the challenges to the human factors are related to unsafe acts, preconditions of unsafe acts, and unsafe supervision. The result reaffirm that human factors should be treated appropriately in the design of reactor equipment and operation procedure as well.Keywords: reactor operation experience, research reactor, human factors, reactor trip